Identification of an Epitope of α-Enolase (a Candidate Plasminogen Receptor) by Phage Display - Arza, Begoña; Félez, Jordi; Lopez-Alemany, Roser; Miles, Lindsey A; Munñoz-Cánoves, Pura (Thrombosis and Haemostasis, 1997)
α-enolase is an ubiquitous cytoplasmic glycolytic enzyme which also exhibits cell surface mediated functions and a structural role in the lens of some species. An α-enolase related molecule (a-ERM) is present on the surfaces of neutrophils, monocytes and monocytoid cells and has the capacity to specifically bind plasminogen, suggesting that a-ERM may function as a plasminogen receptor. We have generated a monoclonal antibody (mAB), 9C12, against a-ERM. This mAB reacted with both α-ERM and purified human α-enolase in Western blotting and in enzyme linked immunosorbent assays (ELISA). mAB 9C12 detected a cell surface associated molecule on human peripheral blood neutrophils and on U937 human monocytoid cells as assessed by fluorescence activated cell sorting (FACS) analyses. In addition, mAB 9C12 recognized an intracellular pool of a-enolase/a-ERM in permea bilized U937 cells. A phage display approach was employed to identify the a-enolase epitope recognized by mAB 9C12. Random fragments of 100-300 base pairs (bp), obtained from the full length human α-enolase cDNA, were cloned into the filamentous phage vector pComb3B, to generate a phage-displayed peptide library. Recombinant phages binding to mAB 9C12 were selected and their DNA inserts characterized by direct sequencing. All of the fragments which bound to mAB 9C12 en coded the common sequence DLDFKSPDDPSRYISP, spanning amino acids 257-272 of human α-enolase. This sequence is located within an external loop of the molecule. These data indicate that this sequence contains the epitope recognized by mAB 9C12 and is, therefore, exposed on the cell surface, further suggesting that a-enolase and a-ERM share common amino acid sequences.